(untitled) (Research, Society and Development, 2021)
The treatment and reuse of effluents have gained prominence in scientific research. Therefore, reducing environmental impacts, solutions associated with the scarcity of water resources, and energy production (biogas) as an alternative to fossil fuels. The objective of this work was to evaluate the potential of methane production and energy generation in the sewage treatment in the city of Poços de Caldas (MG), comparing the economic indicators of the cost of implementing an energy generation plant in these establishments. Three Sewage Treatment Plants (ETE) were selected. The Córrego D’antas and Contorno have a UASB reactor, while Bortolan is composed of a compact system, where the aerobic and anaerobic parts occur in the same reactor. The influent and effluent samples were characterized in the laboratories of DMAE (ETE 1) and Qualin Serviços LTDA (ETE 2 and 3). The parameters evaluated, using the Probio 1.0 software, were the production of biogas and its energy potential, technical-economic analysis of the costs of implementing a power generation plant, investment and operation costs, energy analysis, and economic feasibility. Therefore, it is concluded that only ETE 1 is viable for installing a power plant from biogas generated by sewage treatment, considering its energy production capacity and the return-on-investment time.